Combined Effect of Co-administration of Stromal Cell-Derived Factor-1 and Granulocyte-Colony Stimulating Factor on Rat Model of Alzheimer’s Disease - Komaki, Alireza; Shahidi, Siamak; Hashemi-Firouzi, Nasrin; Rafat, Zahra; Keymoradzadeh, Arman; Golipoor, Zoleikha (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Alzheimer's disease (AD) is a neurodegenerative disease that is characterized by amyloid plaque deposits, neuronal cell loss, and memory impairment. Granulocyte-colony stimulating factor (G-CSF) is a growth factor associated with AD improvement. Stromal cell-derived factor 1 (SDF-1) mediates therapeutic effects of G-CSF. This study investigated the effect of combination treatment of G-CSF and SDf-1 on amyloid plaque deposits, apoptosis, and behavior of AD rats. Methods: Intracerebroventricular amyloid-beta (Aβ (1-42)) peptide was used to induce AD in Aβ rats. There were six groups including naive control, sham-operated, Aβ, Aβ +G-CSF, Aβ + SDF-1, and Aβ +G-CSF+ SDF-1. SDF-1 (ICV), G-CSF Subcutaneous (S.C), or a combination of them were administered to Aβ rats weekly for 2 months. The cognition and memory were assessed using the novel object recognition, passive avoidance, and Morris water maze tests. Next, rat brains were removed and the amyloid plaque and apoptosis were detected in the brain and hippocampus using immunohistochemistry and TUNEL assay, respectively. Results: The amyloid-beta and apoptotic cell levels dropped in groups receiving SDF-1 and G-CSF combination compared to the Aβ group. Also, number of microglial cells increased significantly in the combination group compared to other treatment groups. Moreover, learning and memory were significantly improved in the combination group compared to the Aβ groups (P<0.05). Conclusion: SDF-1 and G-CSF combination therapy can offer a promising strategy for AD.